Nontuberculous mycobacterium in a tertiary tuberculosis center in Iran: Dispensation and outcome of treatment - Payam Tabarsi; Parvaneh Baghaei; Afshin Moniri; Majid Marjani; Ali Akbar Velayati (International Journal of Mycobacteriology, 2015)
Introduction: Nontuberculous mycobacterium (NTM) has clinical and radiological manifestations that are indistinguishable from Mycobacterium tuberculosis (MTB). In an endemic area for tuberculosis (TB), limited data about prevalence and outcome of treatment of these patients is available. In this study the prevalence of different types of mycobacterium and response to treatment in a tertiary referral center in Iran will be evaluated. Materials and method: All NTM cases from 2004 to 2013 at the National Research Institute of Tuberculosis and Lung Diseases (NRITLD) in Iran were extracted from the database. All NTM patients who were treated for NTM diseases entered this study, and the outcome of treatment was evaluated. Results: A total of 104 cases were detected. The mean age was 56.34±15.77 years. Half of the patients were male. Most of the patients had a history of prior TB treatment. The most common types of NTM were Mycobacterium simiae (44 [42.3%]), Mycobacterium kansasii (18 [17.3%]), Mycobacterium abcessus (15 [14.4%]), and Mycobacterium chelonea (14 [13.5%]), respectively. The outcome of treatment was as follows: cure 61 (58.7%), failure 17 (16.3%), relapse 3 (2.9%), default 13 (12.5%) and death in 10 (9.6%) patients. Conclusion: Treatment of NTM had a low cure rate despite low mortality.